Kronik Nilai Etika Orang Jawa Bagi Pertimbangan Moral Orang Indonesia - Pasopati, Rommel Utungga; Djanarko, Indri; Yuliastuti, Anicleta (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2025)
This article exposes the cruciality of Javanese ethical values regarding Indonesian moral considerations. Javanese people always seek for peace in the concept of slamet through conceptions of jagad ageng and jagad alit in Serat Wulangreh and Serat Tripama. The article would like to ask the question whether traditional values contain philosophical understandings especially in Javanese culture. In analysis through qualitative methods through literature study approach, Javanese culture underlines that others are not objects but knowledge of human beings; to consider oneself is to consider others. There is no distance between knowledge and understanding as both are appraised and lived. Humanity is both for oneself individually and for others socially. In conclusion, Javanese values see people to be respected equally in the universe. The main idea is not power or even money, but necessary individual conditions and good social interactions. By stating so, this paper finds its significance especially in how traditional values, especially Javanese, will always exist as a guidance of moral, philosophical, and everyday understandings of human’s life